"African music", a lecture given at Natal University - Cope, Trevor (International Library of African Music, 1959)
The music of Africa is so different from our own music that we are unable to appreciate it until we know where that difference lies and therefore what to listen for. It is no use listening for the harmonies based upon the triads of the major and minor scales when listening to African music. Similarities there are, particularly in the melodic aspect of music. Neither European nor African music is characterised by a high development of melody, such as we find in the rich melodic ornamentation of Indian music. The Indian scale is arranged into a large number of modes (as against our two modes, major and minor) and the octave is divided into 24 quarter-tones (as against our 12 semi-tones), and this gives full scope to the flair for ornamentation to be found not only in the music of India, but also in the wonderful weaving and in other aspects of culture. The intricate patterns of a carpet are analogous to the melodic embellishments of a song; and think of the dome of a Hindu temple.
Keywords: South Africa; Ethnomusicology; Zulu (African people); Musical instruments; Africa; African Music